Portfolio selection and asset pricing models of financial economics and their applications in investing - Baz, Jamil; Guo, Helen; Hakanoglu, Erol (McGraw Hill, 2022)
Top experts from PIMCO deliver a uniquely comprehensive guide for sophisticated investors and advanced graduate students-covering everything from financial mathematics to the practical realities of asset allocation and pricing Investors like you typically have a choice to make when seeking guidance for portfolio selection-either a book of practical, hands-on approaches to their craft or an academic tome of theories and mathematical formulas. Portfolio Selection and Asset Pricing strikes the right balance with an extensive discussion of mathematical foundations of portfolio choice and asset pricing models, and the practice of asset allocation. This guide is conveniently organized into four sections: Mathematical Foundations-normed vector spaces, optimization in discrete and continuous time, utility theory, and uncertainty Portfolio Models-single-period and continuous-time portfolio choice, analogies, asset allocation for a sovereign as an example, and liability-driven allocation Asset Pricing-capital asset pricing models, factor models, option pricing, and expected returns Robust Asset Allocation-estimation of optimization inputs, such as the Black-Litterman Model, shrinkage, and robust optimizers From a top-notch team with impeccable credentials, Portfolio Selection and Asset Pricing provides everything you need to generate long-term profits for your clients while reducing risk"--